Design of an ergonomic tofu cutting tool in the tofu industry of Aceh - Erliana, Cut Ita; Abdullah, Dahlan; Ardian, Zalfie; Siagian, Yusril Yahya (Edelweiss Applied Science and Technology, 2024)
Tofu MSMEs are among those who managed to survive the pandemic, and their numbers continue to grow to this day. However, the number of these MSMEs pales in comparison to the production technology they utilize. The production process in tofu MSMEs still uses traditional methods. One of these methods is used at the cutting workstation. Typically, the tofu cutting workstation lacks specialized tools for tofu cutting, forcing workers to rely on knives and rulers, resulting in repetitive movements during the cutting process. This prolongs the tofu cutting process and results in uneven tofu cuts. Additionally, the manual cutting process and the unsuitability of the cutting area for the workers’ bodies lead to them bending over while cutting. Therefore, many workers complain of pain in their body parts. This research uses the Nordic Body Map questionnaire to identify the body parts of workers experiencing pain and the Rapid Upper Limb Assessment method to assess workers’ posture. This research also uses Catia V5 software for simulating the proposed work posture. The results of the Nordic Body Map assessment show that out of the 21 MSMEs analysed, 4 MSMEs a high level of risk and 17 others have a moderate level. According to the posture assessment results of the six evaluated workers, one tofu SME has a very high-risk level with a score of 7, one tofu SME has a very high-risk level with a score of 6, and four others have a high-risk level with scores of 5. We utilized Catia V5 software to simulate the proposed design of the tofu cutting tool, adjusted to the worker’s body size, and received a score of 3, indicating a medium risk level of musculoskeletal disorders. We expect this tool to reduce risk levels, decrease cutting duration, minimize repetitive motions, and produce more consistent cuts.